Does Ramadan Fasting Adversely Affect Cognitive Function in Young Females?. (30th November 2015) - Ghayour Najafabadi, Mahboubeh; Rahbar Nikoukar, Laya; Memari, Amir; Ekhtiari, Hamed; Beygi, Sara
Abstract : We examined the effects of Ramadan fasting on cognitive function in 17 female athletes. Data were obtained from participants of two fasting (n = 9 ) and nonfasting (n = 8 ) groups at three periods of the study (before Ramadan, at the third week in Ramadan, and after Ramadan). Digit span test (DST) and Stroop color test were employed to assess short-term memory and inhibition/cognitive flexibility at each time point. There were no significant changes for DST and Stroop task 1 in both groups, whereas Stroop task 2 and task 3 showed significant improvements in Ramadan condition (p < 0.05 ). Interference indices did not change significantly across the study except in post-Ramadan period of fasting group (p < 0.05 ). Group × week interaction was significant only for error numbers (p < 0.05 ). Athletes in nonfasting showed a significant decrease in number of errors in Ramadan compared to baseline (p < 0.05 ). The results suggest that Ramadan fasting may not adversely affect cognitive function in female athletes.